Integrative taxonomy of the genus Pseudostegana (Diptera, Drosophilidae) from China, with descriptions of eleven new species - Jinming Lu; Yuan Zhang; Hongwei Chen (PeerJ, 2018)
The genus Pseudostegana (Okada, 1978) currently contains thirty-nine described species. A number of Pseudostegana were collected from the fieldwork in southwestern China from 2010 to 2017. Eleven new species were discovered and are described from southwestern China: Pseudostegana alpina Zhang & Chen, sp. nov.; Pseudostegana amnicola Zhang & Chen, sp. nov.; Pseudostegana amoena Zhang & Chen, sp. nov.; Pseudostegana mailangang Zhang & Chen, sp. nov.; Pseudostegana meiduo Zhang & Chen, sp. nov.; Pseudostegana meiji Zhang & Chen, sp. nov.; Pseudostegana mystica Zhang & Chen, sp. nov.; Pseudostegana stictiptrata Zhang & Chen, sp. nov.; Pseudostegana stigmatptera Zhang & Chen, sp. nov.; Pseudostegana ximalaya Zhang & Chen, sp. nov. and Pseudostegana zhuoma Zhang & Chen, sp. nov. A key to all Chinese Pseudostegana species based on morphological characters is provided. Two mitochondrial loci (COI and ND2) and one nuclear locus (28S rRNA) were sequenced for the Pseudostegana specimens, and Bayesian and RAxML concatenated analyses were run. Molecular species delimitation is performed using the distance-based automatic barcode gap discovery (ABGD) method. Molecular data support the morphological characteristics observed among these Chinese species and confirm the new species as being distinctly different.